2021
DOI: 10.1016/j.ekir.2020.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported Financial Conflict of Interest in Nephrology Clinical Practice Guidelines

Abstract: Introduction There is ongoing controversy concerning the potential influence of industry and financial conflict of interest (FCOI) in the development of clinical practice guidelines (CPG). The influence of industry in renal guideline development has been discussed in the past with emphasis on the National Kidney foundation (NKF) and Kidney and Dialysis Outcomes Quality Initiative guidelines. In this study we evaluate the self-reported FCOI among guideline panel members in Kidney Disease: Improving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The prevalence of Japanese guideline authors with payments ranged from 78% for oncology guidelines (37) to 95% for hematology guidelines (14), and the average annual payments ranged from $10,565 for the oncology guidelines (37) to $28,371 for infectious disease guidelines (38). However, Japanese authors of CKD guidelines may have had more financial COIs compared with those in other countries, as 66% of KDIGO guideline authors self-reported financial COIs with pharmaceutical companies (17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of Japanese guideline authors with payments ranged from 78% for oncology guidelines (37) to 95% for hematology guidelines (14), and the average annual payments ranged from $10,565 for the oncology guidelines (37) to $28,371 for infectious disease guidelines (38). However, Japanese authors of CKD guidelines may have had more financial COIs compared with those in other countries, as 66% of KDIGO guideline authors self-reported financial COIs with pharmaceutical companies (17).…”
Section: Discussionmentioning
confidence: 99%
“…Jefferson and Pearson (31) found that US cholesterol management guidelines and US hepatitis C guidelines deviated from the US National Academy of Medicine standards, and this deviation remained (49). Also, Chengappa et al (17) reported that 90% of KDIGO guidelines had more than half of the guideline authors with reported COIs, which is one of the deviations from the US National Academy of Medicine. All medical societies and organizations developing guidelines should pay more attention to financial COIs with pharmaceutical companies during guideline development and broader nonfinancial COIs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one author failed to self-report FCOI. Many previous studies showed that there were widespread financial conflicts of interest between guideline authors and the healthcare industry in most specialties [13,16,17,19,[27][28][29][30][31][32][33][34][35][36][37]. Most of these studies reported that the majority of the guideline authors received payments from the healthcare industry [3,[38][39][40][41][42][43] and there were large amounts of undisclosed FCOIs with the healthcare industry [13,16,17,34,38,44].…”
Section: Discussionmentioning
confidence: 99%
“…While there are complexities around the influence of industry partners on guideline development, a link between industry payments and favourable nephrology guideline recommendations was reported and discussed extensively following the 2006 update of the KDOQI anaemia guidelines (Supplementary References S8). Recently, major departures by J o u r n a l P r e -p r o o f 8 KDIGO from the national standards for managing financial conflicts of interests (FCOI), alongside the (not necessarily related) conclusion that many KDIGO guidelines are predicated on the weak evidence of expert opinion, has renewed interest in the relationship between industry partners and guideline producers 9 . Clearly, this issue is not unique to nephrology clinical practice guidelines, however adherence to a minimum set of standards for managing FCOI, enforced by journal editors, may enhance synthesis of RCT evidence into guideline recommendations.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%